Socio-Demographic Characteristics and Nutritional Status of Individuals by Stages of Change for Dietary Fat Reduction - Wong, C.Y.; Zalilah, M.S.; Yap, L.D. (Pakistan Journal of Nutrition, 2009)
Changes in lifestyle and food habits have been implicated in the increasing rate of nutrition related chronic diseases in Malaysia. A cross-sectional study was conducted to identify socio-demographic characteristic and nutritional status of individuals by their readiness to reduce dietary fat intake. A total of 202 non-academic staff aged 18-56 years at Universiti Putra Malaysia participated in the study. Information on demographic, socio-economic and stages of change related to dietary fat reduction were collected using a pre-tested interview-administered questionnaire. Subjects were measured for weight, height and waist circumference. Fasting blood through venipuncture was obtained for triglycerides, LDL-, HDL- and total cholesterol. Energy and dietary fat intake were estimated based on two days 24 h diet recall. Chi-square test and Analysis of Covariance (ANCOVA) were used for data analysis. Of the respondents, about 12% reported reduced fat intake, 20% were not committed to change and more than half (68%) were in preparation stage. There was no significant association between stages of change and socio-demographic factors. Body mass index was highest in preparation group (Mean±SE = 24.93±0.35 kg/m2) [F = 5.686; p